2021
DOI: 10.3389/fnins.2021.648489
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Music Therapy via Telehealth: A Survey of Clinician Experiences, Trends, and Recommendations During the COVID-19 Pandemic

Abstract: This cross-sectional survey investigated the transition of Neurologic Music Therapy (NMT) services from in-person (pre-COVID-19) to telehealth (since COVID-19) to (1) determine whether the use of an NMT paradigm contributes to the successful transition of therapy services to telehealth, (2) identify which NMT domains and techniques are transferable from in-person to telehealth, (3) identify whether there are differences in the transition of NMT services across different employment settings, and (4) evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 38 publications
3
26
0
6
Order By: Relevance
“… Street et al (2020) discussed the potential use of touchscreen devices (iPad) in acute stroke rehabilitation as tools to enhance treatment dosage and engagement. More recently, the potential benefits and challenges of adapting in-person therapeutic sessions to remote music therapy services have been examined, with recommendations for the implementation of telehealth into routine care ( Cole et al, 2021 ). Further research to investigate how technology can be incorporated into clinical practice in music-based motor rehabilitation would be of interest.…”
Section: Future Perspectivesmentioning
confidence: 99%
“… Street et al (2020) discussed the potential use of touchscreen devices (iPad) in acute stroke rehabilitation as tools to enhance treatment dosage and engagement. More recently, the potential benefits and challenges of adapting in-person therapeutic sessions to remote music therapy services have been examined, with recommendations for the implementation of telehealth into routine care ( Cole et al, 2021 ). Further research to investigate how technology can be incorporated into clinical practice in music-based motor rehabilitation would be of interest.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Other top challenges were lack of therapist-client personal connection and decreased client engagement. 10 The decreased patient engagement noted in this survey contrasted with our experience of more consistent patient and caregiver engagement in an oncology setting. Perhaps telehealth music therapy is more adaptable in certain settings, where the focus may be to address social-emotional distress rather than cognitive and physical rehabilitation.…”
Section: Discussionmentioning
confidence: 57%
“…A survey of neuro-rehabilitation music therapists providing telehealth music therapy during the COVID-19 pandemic assessed the challenges and benefits of music therapy provided via telehealth. 10 Continuation of regular treatment (36%), decreased travel time (23.2%) and increased accessibility (37.7%) were top benefits noted in the survey, while 68% reported technological difficulties as a top challenge. Other top challenges were lack of therapist-client personal connection and decreased client engagement.…”
Section: Discussionmentioning
confidence: 92%
“…Three recent cross-sectional surveys (Table 2 ) evaluated the pros and cons in the transition of MT from “in person” (pre-COVID-19) to telemedicine services (since COVID-19) taking into account domains and techniques, the possible differences in terms of the occupational context of the music therapist, the potential benefits and future challenges [ 12 14 ].…”
Section: Neurological Music Therapy Services From In Person (Pre-covi...mentioning
confidence: 99%
“…Cole et al [ 12 ] investigated the demographic perception of tele-NMT in terms of technology use, evaluation of safety, clinical practice, role and involvement of the caregiver (CG). Results showed that only few patients interrupted NMT programmes during the transition from “in person” to “telemedicine”.…”
Section: Neurological Music Therapy Services From In Person (Pre-covi...mentioning
confidence: 99%